2020
DOI: 10.18178/ijiet.2020.10.4.1377
|View full text |Cite
|
Sign up to set email alerts
|

A Collaboratively-Developed Enterprise Resource Planning (CD-ERP) Approach in Libyan Higher Education

Abstract: Like other HE institutes in the world, Libyan universities have continuously been working on developing their own ISs or adopting commercial solutions. Both models have shown negative results to some degree. This research was aimed, therefore, to introduce a new model, called: Collaboratively-Developed Enterprise Resource Planning (CD-ERP) to be applied in Libyan Higher Education (LHE). Generally, the model is based on two main principles: ERP packages and community-source. This study comes as the conclusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…As illustrated in Figure 1, the authors examined: firstly the Libyan side, in terms of IS performance, the capability to develop ISs, and other aspects of LHE at university level. The results of the fieldwork in Libya can be found in (Almigheerbi, Ramsey, and Lamek, 2019) (Almigheerbi et al, 2020), while other publications on the topic of the CD-ERP model can be found in (Almigheerbi, Ramsey and Lamek, 2020a, 2020b, 2020c and. Secondly the international side was studied in terms of how such ISs have been implemented and what can be learnt from these experiences.…”
Section: Methodsmentioning
confidence: 99%
“…As illustrated in Figure 1, the authors examined: firstly the Libyan side, in terms of IS performance, the capability to develop ISs, and other aspects of LHE at university level. The results of the fieldwork in Libya can be found in (Almigheerbi, Ramsey, and Lamek, 2019) (Almigheerbi et al, 2020), while other publications on the topic of the CD-ERP model can be found in (Almigheerbi, Ramsey and Lamek, 2020a, 2020b, 2020c and. Secondly the international side was studied in terms of how such ISs have been implemented and what can be learnt from these experiences.…”
Section: Methodsmentioning
confidence: 99%
“…During the study, the author also discovered that it is advised by some similar international projects to start with an existing code for early gains and to avoid negotiations over the basic components of the system. For more information please refer to (Almigheerbi, Ramsey, & Lamek, 2019, 2020.…”
Section: Introductionmentioning
confidence: 99%